In-situ ultrasonic cleaning of crossflow sintered tube microfiltration: effect of sonication cycle time - Wan, Rosmiza Zana Wan Dagang; Rosli , Mohd Yunus; Adnan, Ripin; Dayang, Suhailawati Awang Sulong (Penerbit Universiti Sains Malaysia, 2004)
Membrane separation in general and microfiltration in particular is frequently employed in the dairy, pharmaceutical, food, fermentation and biotechnology, and chemical industries.